Blood Serum Stability Limit and Maximum Storage Time of Bovine Samples - Kovačević, Danijel; Cincović, Marko; Belić, Branislava; Đoković, Radojica; Majkić, Mira (Acta Scientiae Veterinariae, 2021)
Background: Measuring metabolic parameters in the blood has been an indispensable tool for assessing the productive and health status of dairy cows for more than 100 years. The values of laboratory parameters depend on various preanalytical, analytical and postanalytical factors. The most important preanalytical factors are sample transport time and temperature, hemolysis, anticoagulant type, and sample volume.Preanalytical factors can lead to reduced stability of the analyte in the sample, which changes their concentration. Loss of stability changes the time of storage and manipulation of the sample, which determines the criteria for its acceptance or rejection. The two stability indicators are stability limit and maximum permissible instability. A stability limit (SL) is defined as the period of time in which a property variation does not exceed a maximum permissible instability (MPI). The aim of this study was to determine the SL and MPI for each analyte in the blood serum of cows and to determine whether SL differs in the function of the presence of preanalytical errors in the blood sample. Materials, Methods & Results: Three hundred samples of dairy cow origin in different periods of lactation participated in this research. They were classified into 6 groups of 50 samples: according to the time from sampling to processing in the laboratory (0-4 h, 4-8 h and over 8 h; all transported on dry ice, protected from environmental factors, without preanalytical errors) and according to the presence of preanalytical errors (group with hemolysis, a group transported at ambient temperature and a group with a small sample volume). Each sample was aliquoted in two portions. One portion was left at +4°C and tested once a day for 6 days of sample storage, and the second portion, placed at -20 °C, was tested once a month for 6 months. The MPI had a value ranging from 1.55 to 8.4. Metabolic profile analytes with lower MPI values (1.51-3.22) were albumin (ALB), total protein (TPROT), UREA, glucose (GLU), calcium (Ca), and phosphorus (P). Higher MPI values (5.1-8.3) were found for nonesterified fatty acids (NEFA), beta-hydroxybutirate (BHB), cholesterol (CHOL), triglycerides (TGC), total bilirubin (TBIL) and aspartat aminotransferase (AST). For most parameters, we can conclude that their PD% changed faster in storage conditions at +4 °C compared to the regime of -20 °C. The largest number of biochemical analytes in bovine blood serum shows preserved stability in the first 6 days at +4°C or 6 months at -20°C if transported to the laboratory within 8 h after sampling in ideal conditions and without the action of preanalytical errors. Prolonged transport under ideal conditions or the existence of preanalytical errors such as transport at room temperature, hemolysis or small sample volume shorten the stability of the ALB, NEFA, GLU, UREA and P. Concentration of all analytesdecreasesduring the stability test except for UREA, NEFA, BHB and for CHOL and TGC in some groups. Variations in parameters such as BHB, NEFA, TBIL, AST, and Ca have shown potential clinical significance. At storage conditions at +4°C, clinically significant variations at at least one measurement point were found for AST (7.5% of samples), BHB (6.1% of samples), NEFA (9.9% of samples) and for TBIL (in 7% of samples). Discussion: This study can help define acceptable delay times and storage conditions for bovine blood samples, which is of great importance because in working with farm animals it is often not possible to take samples in a short time and deliver them to the laboratory, and samples are often burdened with certain preanalytical errors with limited possibilities of re-sampling.